Comparison of the effects of neuromuscular electrical stimulation plus conventional treatment to those of conventional treatment alone in patients with fibromyalgia: A randomized controlled study - Elbasti, Muhammet Sahin; Yentur, Songul Baglan (Lippincott Williams & Wilkins, 2025)
Background: The aim of this study was to investigate the effects of neuromuscular electrical stimulation (NMES) in addition to the conventional treatment (CT) on pain, quality of life, sleep quality and posture, and compare with CT alone. Methods: This study included 40 female patients with fibromyalgia. Pain intensity, sleep quality, quality of life and posture were evaluated with visual analog scale, Pittsburg Sleep Quality Index, Fibromyalgia Impact Questionnaire and New York Posture Rating Chart, respectively. Patients were divided in 2 groups randomly. First group was applied NMES + CT and second group was applied CT alone. The interventions were lasted for 6 weeks. Results: No statistically significant differences was found between groups in demographic variables. After treatment, a statistical difference was found between the 2 groups only in pain intensity (P = .015). Significant differences were concluded in comparison of before and after treatment in both groups (P < .05). In addition, significant difference between the groups in pain (P = .006) and posture (P = .014) in the comparison of delta (Delta) measurements between groups. Conclusion: Additional NMES application was found superior on pain and posture compared to CT alone in patients with fibromyalgia syndrome. Adding NMES to the routine treatment may increase the success of fibromyalgia syndrome rehabilitation.
Keywords: conventional treatment; fibromyalgia syndrome; neuromuscular electrical stimulation